Characterization of Propolis Extracts Prepared Using Different Solvents at the Different Concentrations - Özkök, Aslı; Keskin, Merve; Tanuğur Samancı, Aslı Elif; Önder, Elif Yorulmaz; Takma, Çiğdem (Progress in Nutrition, 2021)
Propolis is an important bee product with many biological activities such as antibacterial, antiviral, antifungal. However, it has a complex structure as it contains many components such as beeswax, balm, pollen, flavonoids, and phenolic acids. Useful components of this structure must be dissolved in an effective and reliable solvent in order to be released. In this study, propolis samples were collected from different regions of Turkey and these samples dissolved in various solvents with different concentrations (70% glycol was used for water-soluble propolis extracts of 10% and 15%, and 70% ethanol was used for ethanol extracts of 20% and 30%) for the preparing extracts. Then, in these extracts, dry matter, total phenolic, total flavonoid and antioxidant capacity were determined and compared. A statistically significant difference was found between the results of all the concentrations examined in this study (p<0.01). In addition, as a result of the results obtained, 20% ethanol extract (70% v/v ethanol) and 15% glycol propolis extract (70% v/v glycol) are statistically similar; and 30% ethanol propolis extract (70% v/v ethanol) was found to contain the most bioactive components (p<0.01).